Some parameters affecting the distributional properties of operant-level running in rats - Premack, David (1963)
Six adult female albino rats were subjected to operations known to increase the frequency of wheel-running. Operations included limited access to wheel, food deprivation, and protracted maintenance on a 24-hr feeding schedule. A distributional analysis of response duration, burst duration, and inter-burst interval showed that the increased frequency in all cases arose mainly from a shortening of the interval between successive bursts. Only short-term food deprivation produced any notable increase in burst length, and even here changes in both speed of the individual responses and in number of responses per burst were slight compared to changes in inter-burst interval.